Pendampingan, Evaluasi dan Pelatihan Pembuatan Buku Ajar Digital Matematika Kurikulum Merdeka Bagi Guru SDIT Fitrah Insani Langkapura - Novalia Novalia; Septia Uswatun Hasanah; Fitria Rahmawati; Nurul Isnaini; Rika Pramudita (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This community service activity was conducted to address issues at SDIT Fitrah Insani, such as the misalignment of teaching materials with the Merdeka Curriculum, the use of language that does not match student characteristics, and the need for developing digital teaching materials in the form of Flipbooks. The goal of this activity was to assist teachers in developing mathematics teaching materials that align with the Merdeka Curriculum and provide training on creating Flipbooks. The methods used included mentoring, evaluating teaching materials, and Flipbook training. This activity involved 56 teachers from SDIT Fitrah Insani and was held at Universitas Sang Bumi Ruwa Jurai from June to September 2024. The evaluation results indicated that the teaching materials produced met curriculum standards and used appropriate language. Additionally, there was a significant improvement in teachers' understanding of digital teaching material development and their ability to create materials that align with the curriculum and student characteristics.